The Passover Haggadah : a biography - Ochs, Vanessa L. (Lives of great religious books., 2020)
"This telling of the life of the Haggadah, probably the most beloved of books that Jews own, chronicles its recalibrations over time. It moves from its early sources in the Bible and rabbinic literature; to the years it was a handwritten manuscript; to its life as an illuminated book in the middle ages; to its emergence as mass-produced printed book and later, as an artist's book; to its iterations in the twentieth century in America and Israel, including those using emerging technologies of our day. It is the story of a liturgical text came about to fulfill a biblical injunction to fathers to tell the story of the Exodus from Egypt to their children (literally, to their sons): "And you shall tell your son on that day, 'It is because of what the Lord did for me when I went free from Egypt'" (Exodus 13:8). Despite significant flaws in the text that have occasioned thousands of revisions, it remains well and alive because it allows its users to transmit the story of Exodus as if it happened to them. With a Haggadah in hand at a Passover seder meal, the text kindles the memory of belonging to a people who knew slavery and then liberation and enlivens empathy. An engagement with the Haggadah, inevitably leaves one feeling responsible for helping others to achieve their own liberation"--